Windows of fame : a heroic chronicle of Australians at war - Harding, Bruce A., (Bruce Alfred), 1920- (Lansdowne Press, 1963)
15 remarkable stories to illuminate the meaning of each symbolic window in the Hall of Memory of the Australian War Memorial, Canberra.